Nonlinear fatigue life prediction model based on the theory of the S‐N fatigue damage envelope. Issue 5 (8th March 2022) - Bjørheim, Fredrik; Pavlou, Dimitrios G.; Siriwardane, Sudath C.
Abstract: A nonlinear model is proposed in light of the theory of isodamage curves, to assess the cumulative fatigue damage under multistage loading. The isodamage curves were developed through the theory of the S‐N fatigue damage envelope, proposed by Pavlou. The adopted functional form of the fatigue damage is a commonly accepted general form. In the present work, a stress function for the fatigue life exponent is derived with the aid of the S‐N curve only. In the proposed nonlinear model, no adjusting parameters are necessary for fatigue damage estimation. The fatigue life prediction of the derived model is compared with experimental results of various alloys and existing models. The comparison is made for C35, C45, Al‐2024‐T42, 15HM, A336 GR 5, and A387 GR22 for two‐stage loading high‐low and low‐high, and Al 6082‐T6 for multistage loading. Highlights: Nonlinear damage function in light of the theory of the S‐N fatigue damage envelope Validity of the model in both HCF and LCF Verification of the new fatigue model with various metallic materials Discussion of the model effectivenes in relation to the known fatigue damaging process